Time Multiplexed Binary Offset Carrier (TMBOC) Transmitter with Polarimetric Interferometric Synthetic Aperture Radar (Pol-InSAR) - Sayanti Dutta; Rintu Kumar Gayen; Raisa Chatterjee; Tamesh Halder (International Journal of Satellite Remote Sensing, 2026)
This paper provides insights into Time Multiplexed Binary Offset Carrier (TMBOC), a modulation technique employed in satellite navigation systems, specifically designed for GPS L1C. TMBOC improves signal correlation properties by time-multiplexing Binary Offset Carrier (BOC) (1, 1) and (6, 1). The text discusses various TMBOC models, including spectral representations and power distributions. Performance analysis reveals the potential of TMBOC signals in achieving superior tracking accuracy and interference resistance compared to other modulation techniques. Spectrum allocation considerations for TMBOC in the GPS L1 band are addressed. The information underscores the significance of TMBOC in enhancing the robustness and precision of satellite navigation systems, contributing to the continual evolution of signal modulation strategies in this technological domain. The literature on PolInSAR and PolSAR assesses the various techniques for estimating the forest height, biomass, and complex coherence. The study involves complex Wishart distribution-based methods and target decomposition-based methods. These techniques have the potency to demonstrate and retrieve the vegetation parameters and perform various land cover-based classifications. The images taken by radar have to be linked with GPS co-ordinates and ground control points for making digital surface model (DSM). This work is done at base stations while the GPS signals and images are received at master control units (MCU). Hence the thorough study and simulation of current state of arts in navigation paves the way of geographic-information systems (GIS) with remote sensing. The article bridge the GPS of current era modulation technique TMBOC and radar image Polarimetric Interferometric Synthetic Aperture Radar (Pol-InSAR).
Keywords: GPS L1 Band; Pol-InSAR; PolSAR; RVoG; Signal Correlation; Signal Modulation; Spectral Representations; Spectrum Allocation; Time Multiplexed Binary Offset Carrier (TMBOC); Vegetation height determination